2022
DOI: 10.1155/2022/3861518
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Elicits Type I Interferon Response in Human Monocytes via Toll-Like Receptor 8 Signaling

Abstract: Helicobacter pylori colonization and persistence could precede gastric adenocarcinoma. Elucidating immune recognition strategies of H. pylori is therefore imperative to curb chronic persistence in the human host. Toll-like receptor 7 (TLR7) and TLR8 are widely known as viral single-stranded RNA (ssRNA) sensors yet less studied in the bacteria context. Here, we investigated the involvement of these receptors in the immunity to H. pylori. Human THP-1 monocytic cells were infected with H. pylori, and the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Recent studies have revealed a significant correlation between zinc status and Toll-like receptors in the body, which could impact infection and immune function in children ( 41 ). Moreover, Toll-like receptors play a crucial role in Helicobacter pylori infection ( 42 ). As part of the innate immune system, Toll-like receptors act as the first line of defense against bacterial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed a significant correlation between zinc status and Toll-like receptors in the body, which could impact infection and immune function in children ( 41 ). Moreover, Toll-like receptors play a crucial role in Helicobacter pylori infection ( 42 ). As part of the innate immune system, Toll-like receptors act as the first line of defense against bacterial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…TLR7 is also implicated in other infection diseases, such as Pseudomonas aeruginosa pneumonia or Helicobacter pylori infection, and TLR7 or TLR7/8 antagonist might play a positive role in bacterial recognition and treatment [ 85 , 86 , 87 ].…”
Section: Tlr7 Implication In a Variety Of Clinical Diseasesmentioning
confidence: 99%
“…The phosphorylation of IRF7 is linked to PRR pathways. TLR7/8 antagonists reduce Helicobacter pylori infection-mediated IRF7 phosphorylation ( 51 ). Kinases such as IKKϵ, TBK1, IRAK1 and IKKα are responsible for the phosphorylation of IRF7 in a cell type-specific manner ( 52 , 53 ).…”
Section: The Function Of Irf7mentioning
confidence: 99%